2009
DOI: 10.1248/bpb.32.1552
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Anticancer Effects of American Ginseng Berry: Exploring Representative Compounds

Abstract: Human colorectal cancer is a common malignancy with a 2008 recorded incidence of 148810 cases with a mortality of 49960 in the United States alone. 1) Half of all patients diagnosed with colorectal cancer eventually will die from the disease; and only less than 10% of patients with metastatic colorectal cancer will survive more than five years after diagnosis. Although many early stage colorectal cancers are cured by surgical resection alone, most often, surgery is combined with adjuvant radio-and chemotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 31 publications
0
40
0
Order By: Relevance
“…However, for the past decade investigations have demonstrated the direct anticancer properties possessed by ginseng and its active anticancer compounds ginsenosides (14-18,72). We previously evaluated the cancer chemopreventive activities of American ginseng root extract (AGE and S-AGE) and fraction (S2h) on human colorectal and breast cancer (27). Our microarray data indicated that the expression levels of 76 genes were changed significantly after treatment with S2h or Rg3 in HCT116 cells (28).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, for the past decade investigations have demonstrated the direct anticancer properties possessed by ginseng and its active anticancer compounds ginsenosides (14-18,72). We previously evaluated the cancer chemopreventive activities of American ginseng root extract (AGE and S-AGE) and fraction (S2h) on human colorectal and breast cancer (27). Our microarray data indicated that the expression levels of 76 genes were changed significantly after treatment with S2h or Rg3 in HCT116 cells (28).…”
Section: Discussionmentioning
confidence: 95%
“…Several ginsenosides (e.g., Rh2, Rg3, and Rk1) exhibit anti-proliferative and antiangiogenic activities in vitro and in vivo (19)(20)(21). Mechanistically, Rg3 and/or Rh2, Rk1, has been shown to inhibit the NF-κB signaling pathway (22) and cell proliferation, and to induce apoptosis in cancer cell lines (23)(24)(25)(26)(27)(28). Nonetheless, ginsenosides exhibit a broad range of biological activities, including anticancer activities; and their molecular modes of actions may be diverse and remain largely undefined.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on ginsenosides especially Rg3 and Rh2 showed that they are most effective anti-cancer compounds identified in ginseng (Kim et al, 2004;Helms 2004;Li et al, 2009;Liu et al, 2009;). East Asian countries Asian Panax ginseng is steamed and is called red ginseng, red ginseng air dried is called white ginseng .Studies have shown that anti-cancer effects of red ginseng are stronger than white ginseng Xie et al, 2009). The steaming process alters ginseng content and is a good way to convert all kinds of ginsenosides to strong anticancer compounds such as Rg3 and Rh2 ).…”
Section: Effect Of Ginseng On Colorectal Cancermentioning
confidence: 99%
“…In addition to direct inhibition of cell growth [7], Rg3 arrests the cancer cell cycle [8], inhibits angiogenesis [9], and elicits cell apoptosis [10].…”
Section: Introductionmentioning
confidence: 99%